Multi-Energy Threshold-based Routing Protocol for Wireless Sensor Networks - Mansura, A. (Institute of Electrical and Electronics Engineers Inc., 2019)
Recently, Wireless Sensor Network (WSN) has received increased interest of research due to its many real-life applications. In WSNs, the sensor nodes sense different phenomenon from the surrounding area and forward data to the sink. Among the available routing protocols (RP), most of them used Low Energy Adaptive Clustering Hierarchy (LEACH) but did not consider the battery energy level while selecting the cluster head (CH). This paper proposed a multi-energy threshold-based routing protocol based on LEACH, which provides different energy thresholds of battery energy level, called multi-energy threshold LEACH (MET-LEACH). The MET-LEACH uses remaining battery energy level to select the CHs. The first node dies (FND), the half nodes die (HND), the last node dies (LND), packet reception ratio (PRR) and the application level latency are the performance parameters to evaluate the performance of the proposed MET-LEACH protocol using the Castalia simulator. The simulation results show that MET-LEACH gives significant improvement in terms of FND (112 to 290), HND (76 to 161) and LND (76 to 185) over the performance of LEACH. Â© 2019 IEEE.